2017
DOI: 10.1007/s00405-017-4602-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of quercetin in an experimental rat model of allergic rhinitis

Abstract: We aimed to investigate whether quercetin had a therapeutic effect in an experimental rat model of allergic rhinitis. The study was conducted with 35 rats, which were randomly assigned into 4 groups: group 1 (n = 5), sham group; group 2 (quercetin group, n = 10) received 80 mg/kg day quercetin; group 3 (steroid group, n = 10) received steroid (mometasone furoate); and group 4 (control group, n = 10), received ovalbumin alone. Rats were sensitized by administration of ovalbumin on alternate days over 14 days vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The United States Food and Drug Administration has already approved oral doses of quercetin as safe for human consumption. Quercetin given nasally was effective in a rat model of allergic rhinitis [12], and the safety of quercetin has been favourably assessed [13]. Quercetin at high doses, like any other bioactive compound, could have potentially off-target effects.…”
Section: Doses Requiredmentioning
confidence: 99%
“…The United States Food and Drug Administration has already approved oral doses of quercetin as safe for human consumption. Quercetin given nasally was effective in a rat model of allergic rhinitis [12], and the safety of quercetin has been favourably assessed [13]. Quercetin at high doses, like any other bioactive compound, could have potentially off-target effects.…”
Section: Doses Requiredmentioning
confidence: 99%
“…In previous studies, quercetin has been found to inhibit mast cell activation, inflammatory cytokine production, and histamine release after immunological stimulation. Quercetin may suppress AR in rats by increasing Cl transport and ciliary beat frequency [41]. Quercetin modulates the activation of inflammatory cells and neuropeptide production and results in improvement of clinical conditions of allergic diseases, especially AR [42].…”
Section: Resultsmentioning
confidence: 99%
“…In immune histochemical evaluation, it was detected that COX-2 and vasoactive intestinal polypeptide (VIP) expressions were weaker in the quercetin group than the control group. According to these findings, they concluded that quercetin was effective in AR-induced by OVA in rats both histopathologically and serologically [45] (Table 2).…”
Section: In Vivo Studiesmentioning
confidence: 96%